Differential effects of buffer pH on Ca2+-induced ROS emission with inhibited mitochondrial complexes I and III - Lindsay, Daniel P.; Camara, Amadou K. S.; Stowe, David F.; Lubbe, Ryan; Aldakkak, Mohammed (Frontiers in Physiology, 2015)
Excessive mitochondrial reactive oxygen species (ROS) emission is a critical component in the etiolo-gy of ischemic injury. Complex I and complex III of the electron transport chain are considered the primary sources of ROS emission during cardiac ischemia and reperfusion (IR) injury. Several factors modulate ischemic ROS emission, such as an increase in extra-matrix Ca2+, a decrease in extra-matrix pH, and a change in substrate utilization. Here we examined the combined effects of these factors on ROS emission from respiratory complex I and III under conditions of simulated IR injury. Guinea pig heart mitochondria were suspended in experimental buffer at a given pH and incubated with or without CaCl2. Mitochondria were then treated with either pyruvate, a complex I substrate, followed by rote-none, a complex I inhibitor, or succinate, a complex II substrate, followed by antimycin A, a complex III inhibitor. H2O2 release rate and matrix volume were compared with and without adding CaCl2 and at pH 7.15, 6.9, or 6.5 with pyruvate + rotenone or succinate + antimycin A to simulate conditions that may occur during in vivo cardiac IR injury. We found a large increase in H2O2 release with high [CaCl2] and pyruvate + rotenone at pH 6.9, but not at pHs 7.15 or 6.5. Large increases in H2O2 release rate also occurred at each pH with high [CaCl2] and succinate + antimycin A, with the highest levels observed at pH 7.15. The increases in H2O2 release were associated with significant mitochondrial swelling, and both H2O2 release and swelling were abolished by cyclosporine A, a desensitizer of the mitochondrial permeability transition pore. These results indicate that ROS production by complex I and by III is differently affected by buffer pH and Ca2+ loading with mPTP opening. The study sug-gests that changes in the levels of cytosolic Ca2+ and pH during IR alter the relative amounts of ROS produced at mitochondrial respiratory complex I and complex III.